2017
DOI: 10.12659/msm.905951
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epithelial Cell Transforming Sequence 2 (ECT2) in Predicting Prognosis of Osteosarcoma

Abstract: Background:Osteosarcoma is a major bone malignancy in children and young adults, and it is highly heterogeneous. The clinical outcome of osteosarcoma is individual-dependent due to different genetic and pathological profiles. Although chemotherapy in combination with surgery has significantly improved the survival of localized disease, the prognostic improvement for metastatic patients is less marked. ECT2 (epithelial cell transforming sequence 2) is a transforming protein that can interact with Rho-like prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The oncogene ECT2 is a guanine nucleotide exchange factor (GEF)of the Rho family members of small GTPases and essential for signal transduction pathways involved in the regulation of cytokinesis. Chen et al [57] . showed that overexpression of ECT2 promoted the metastasis of osteosarcoma by regulating the EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogene ECT2 is a guanine nucleotide exchange factor (GEF)of the Rho family members of small GTPases and essential for signal transduction pathways involved in the regulation of cytokinesis. Chen et al [57] . showed that overexpression of ECT2 promoted the metastasis of osteosarcoma by regulating the EMT process.…”
Section: Discussionmentioning
confidence: 99%
“…14,38 Such crosslinkers should also affect the inter-filament distance. 13,30,39,40 In order to find potential cross-linking sites we undertake an electrostatic ''handshake'' analysis of the NF tails. 30 We evaluate short-range electrostatic attractive interactions, between tails, using a coarse-grained model; where segments engage in a zipper-like electrostatic interaction.…”
Section: Electrostatic Analysis Reveals Multiple Ionic Cross-linking mentioning
confidence: 99%
“…Xu et al [55] have reported that the downregulation of ECT2 by miR-223 induces the expression of p21 and p27, which restrain cell cycle progression and proliferation in osteosarcoma cells. Furthermore, according to Chen et al [19], ECT2 could promote osteosarcoma cell invasion by facilitating the epithelialmesenchymal transition. In addition to miRNAs, several signalling molecules have been identified as up-stream regulators of ECT2 expression in cancer cells; these promote cancer progression in an ECT2-dependent manner.…”
Section: Discussionmentioning
confidence: 97%
“…A total of 19 published articles with 21 studies enrolling 5,305 patients met the inclusion criteria for the meta-analysis [11,15,[19][20][21][22][23][24][25][32][33][34][35][36][37][38][39][40][41]. A flow diagram of the detailed literature selection process is displayed in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation